Stability analysis and evaluation of surrounding rock of ultra-deep shaft under complicated geological conditions - Hou, Kuikui; Zhu, Mingde; Hao, Yingjie; Yin, Yantian; An, Long (Frontiers in Earth Science, 2023)
Abstract: The construction of deep underground engineering will face complex geological conditions such as high stress, faults and fracture zones, which affect significantly on the stability of the project. Taking the construction of 1915 m deep shaft in Sanshandao Gold Mine as the engineering background, which pass through many different strata and multiple fracture zones. The stability evaluation and failure zone prediction during its excavation under the influence of high stress, uneven strata and fault structure are studied. Results show that the range of failure zone will increase significantly when the shaft passes through the fracture zone or different lithology, and the maximum depth is 5.28 m. When the distance between rockmass in borehole and the excavation face is greater than 48 m, the disturbance superposition effect basically disappears. This paper will provide theoretical and data support for the design and construction of kilometer deep shaft in Sanshandao Gold Mine.